Parents Responses: The Use of Gadgets in Early Childhood - Fadila, Arini; Wardhani, Junita Dwi (Jurnal Pendidikan Indonesia, 2022)
A gadget is an electronic device that has a special function, from time to time gadgets are increasingly developing by getting new innovations to add features and technology that are more comfortable and practical so that they can make it easier in everyday life. The impact of the development of technology itself is that children are more fond of playing gadgets because they are a means of learning and playing. The most influential figure in responding to the use of gadgets is parents, so parents have a big role in guiding and preventing gadget technology from having a negative impact on children. This study aims to analyze the differences in the role of parents in responding to the use of gadgets in early childhood by comparing the preventive and curative efforts. This study used a quantitative approach using a total sampling technique and testing the hypothesis using a one way ANOVA test by taking a sample of 50 parents. The results of this study are that parents' preventive efforts are better and more widely applied by parents compared to curative efforts. This is evidenced by the average value of preventive efforts of 76.0600 and the average value of curative efforts of 51.1400. So with the acquisition of these values, it can be concluded that preventive efforts have a higher score than curative efforts made by parents in addressing the use of gadgets in early childhood.